TEACHING SUBJECT-VERB AGREEMENT OF ENGLISH GRAMMAR A HANDBOOK FOR TESL TEACHER - Sarala Thulasi Palpanadan (Penerbit UTHM, 2019)
This book is hoped be helpful to English language teachers and students to explore and learn about Subject-Verb Agreement (SVA) in English language learning. The writer as a student and later as an English language teacher and lecturer found it a major challenge to teach English generally and grammar specifically. It is a common phenomenon in Malaysian English as a Second Language (ESL) classrooms that teachers find it challenging to teach and students find it perplexing to learn this important language principle. The writer of this book discovered that this important grammar principle (referring to SVA rules) has deeply affected students’ language learning and teachers’ language teaching based on her classroom observations and professional experiences. Hence, keeping in view of the need for the students and teachers, the writer researched into this area thoroughly.